Influence of Solvents on the Electroactivity of PtAl/rGO Catalyst Inks and Anode in Direct Ethanol Fuel Cell - Thu Ha Thi Vu; Minh Dang Nguyen; Anh Tuan Ngoc Mai (Journal of Chemistry)
This paper presents research on the effects of common solvents such as n-butyl acetate, isopropanol, and ethanol on the properties and electroactivity of catalyst ink based on PtAl/rGO. The inks prepared by mixing PtAl/rGO catalyst, Nafion solution (5 wt%), and solvent were coated on carbon cloth by the spin coating method. The results obtained showed that ethanol was the most suitable solvent for the preparation of catalyst ink with a volume ratio between catalyst slurry and solvent of 1 : 1 (CI-EtOH (1/1) ink). The surface of the CI-EtOH (1/1) coated electrode was smooth, flat, and even and had no cracks due to the increase of Nafion mobility, resulting in significant improvement in the interaction between Pt particles and ionomer. Moreover, the electrochemical activity of the CI-EtOH (1/1) ink in ethanol electrooxidation reaction, in both acidic and alkaline media, has the highest value, with the forward current density, IF, reaching 1793 mA mgPt−1 and 4751 mA mgPt−1, respectively. In the application in direct ethanol fuel cell (DEFC), the CI-EtOH ink-coated anode also exhibited the highest power density in both PEM-DEFC (with a proton exchange membrane) and AEM-DEFC (with an anion exchange membrane) at 19.10 mW cm−2 and 27.07 mW cm−2, respectively.